1996
DOI: 10.1172/jci118552
|View full text |Cite
|
Sign up to set email alerts
|

Fc gamma RIIA alleles are heritable risk factors for lupus nephritis in African Americans.

Abstract: Allelic variants of Fc ␥ R confer distinct phagocytic capacities providing a mechanism for heritable susceptibility to immune complex disease. Human Fc ␥ RIIa has two codominantly expressed alleles, R131 and H131, which differ substantially in their ability to ligate human IgG2. The Fc ␥ RIIa-H131 is the only human Fc ␥ R which recognizes IgG2 efficiently and optimal IgG2 handling occurs only in the homozygous state. Therefore, since immune complex clearance is essential in SLE, we hypothesized that Fc ␥ RIIA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
293
1
9

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 457 publications
(323 citation statements)
references
References 42 publications
20
293
1
9
Order By: Relevance
“…The etiology of SLE has a definite genetic component as inferred from increased familial aggregation among siblings and an increased concordance rate among monozygotic twins compared to dizygotic twins. [1][2][3] This is further supported by the identification of genetic associations of candidate gene polymorphisms 4,5 as well as the establishment of linkage to loci in genome-wide scans in SLE. [6][7][8][9][10][11][12] In man, SLE is not often a single gene disorder; the genetic effect generally appears to be conferred by polymorphisms in multiple genes.…”
Section: Introductionmentioning
confidence: 92%
“…The etiology of SLE has a definite genetic component as inferred from increased familial aggregation among siblings and an increased concordance rate among monozygotic twins compared to dizygotic twins. [1][2][3] This is further supported by the identification of genetic associations of candidate gene polymorphisms 4,5 as well as the establishment of linkage to loci in genome-wide scans in SLE. [6][7][8][9][10][11][12] In man, SLE is not often a single gene disorder; the genetic effect generally appears to be conferred by polymorphisms in multiple genes.…”
Section: Introductionmentioning
confidence: 92%
“…FcyRIIA genotyping was performed by polymerase chain reaction amplification of genomic DNA from peripheral blood leukocytes, using allele-specific primers as previously described (10). Four of the 5 patients were determined to be homozygous for the R131 allele, while the fifth (patient 5) was an R131/H131 heterozygote.…”
Section: Fcyriia Polymorphism As a Risk Factor For Invasive Pneumococmentioning
confidence: 99%
“…The increased gene frequency of FcyRIIA-R131 in SLE (and particularly in lupus nephritis, in which the allelic frequency is up to 65%) defines these patients as a population with an inherently increased predilection for invasive pneumococcal infections (10). This independent risk may act synergistically with other concomitant conditions, such as splenic dysfunction, hypocomplementemia, and immunosuppression, to potentiate propensity for infections by encapsulated organisms like Spneumoniae.…”
Section: Fcyriia Polymorphism As a Risk Factor For Invasive Pneumococmentioning
confidence: 99%
“…8 We have recently found that FcgRIIc is predominantly expressed on NK cells and that it is able to trigger NK cell lysis of antibody-coated target cells and cytokine production. [9][10][11] Allelic polymorphisms of FcgR genes have been described 9,[12][13][14][15] that affect the function of cells of the innate immune system including FcgRIIIA, 14,16 FcgRIIA, 17 FcgRIIC, 7,18 and FcgRIA. 19 In general, these polymorphisms have been shown to alter the ligand binding specificity of particular FcgR, such as FcgRIIa, 17 and FcgRIIIa.…”
Section: Introductionmentioning
confidence: 99%
“…19 In general, these polymorphisms have been shown to alter the ligand binding specificity of particular FcgR, such as FcgRIIa, 17 and FcgRIIIa. 14,16 These allelic polymorphisms have proved to be clinically significant in infectious 20,21 and autoimmune 12,13,[22][23][24] diseases.…”
Section: Introductionmentioning
confidence: 99%